Idârah Tanzhîm Barnâmij Mukhayyam al-Lughah al-‘Arabiyah li Ittihâd Thalabah al-Lughah ‘Arabiyah bi Indonesia - Nurul Hidayat; Raenza Agung Pratama; Zakiya Arifa (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
This research will explore the type or form of structure for managing the organization of the Arabic language camp program of the Fourth Sub-Government Board of the Arabic Language Students Association (ITHLA) in Indonesia, and the steps in managing its organization. This research uses a qualitative descriptive research method. Data is collected using interview and documentation techniques. The researchers obtain data from the former Chairman of the Board of Directors and one of the committee members. After collecting the data, the data is analyzed through; Display data, reduce data. As for the results from this research, it is concluded that the type of organization used in the Arabic language camp program is a functional organizational type by grouping committees that have the same skills and tasks into work groups (one department) and in the department work on the basis of job placement. In this research there are several language programs; Public speaking competition, Arabic debate competition, book reading competition, Arabic singing competition, Arabic poetry reading competition, National Scientific Forum, International Scientific Forum, and activating the Arabic language environment during the program process.